Amorphous SnO2/graphene aerogel nanocomposites harvesting superior anode performance for lithium energy storage. (1st August 2016) - Fan, Linlin; Li, Xifei; Yan, Bo; Li, Xiaojia; Xiong, Dongbin; Li, Dejun; Xu, Hui; Zhang, Xianfa; Sun, Xueliang
Graphical abstract: Highlights: The amorphous SnO2 /graphene aerogel were successfully synthesized. The nanocomposites showed high reversible capacity and cycling stability. The study exhibited an effective strategy for anode materials of LIBs. Abstract: The Sn-based materials have been hindered from practical use for lithium ion batteries due to the inherent volume change leading to poor cycling performance. To mitigate this challenge, in this study, amorphous SnO2 /graphene aerogel nanocomposites are fabricated via a simple hydrothermal approach. The amorphous nature of SnO2 is clearly determined in detail by transmission electron microscopy, aberration-corrected scanning transmission electron microscopy, and X-ray diffraction measurement. The as-prepared material shows satisfying reversible capacity and significant cyclic stability. For instance, it delivers an excellent discharge capacity of 700.1 mA h g −1 in 80th cycle at a current density of 100 mA g −1, in accordance with a high retention capacity of 97.6% compared to that of the sixth cycles, which is much better than crystalline SnO2 /graphene aerogel. The enhanced electrochemical performance can be ascribed to the intrinsic isotropic nature, smaller size, and high electrochemical reaction kinetics of amorphous SnO2, together with the graphene aerogels matrix. Therefore, this study may provide an effortless, economic, and environmental friendly strategy to fabricate high volume change electrode materials for lithium ion batteries.